Leveraging technology to enhance impact measurement of SMMEs and social enterprises in South Africa - Venter, Marelize (Graduate School of Business (GSB), 2022)
The global economy as we know it is changing: stakeholders' priorities have shifted towards businesses that provide demonstrable impact on their communities and the environment. But are South African Small-, Micro- and Medium- Enterprises (SMMEs) prepared to rise to the challenge of measuring and communicating their impact? The adoption of Impact Measurement among enterprises has scarcely been covered in empirical literature, where the limited research available has put a strong emphasis on impact measurement for investors, and not necessarily the enterprises creating the impact. Furthermore, there is a dearth of information available on the use of Impact Measurement in South Africa, arguably a country desperate for effective, impact-driven capital allocation. Technology provides the opportunity to make Impact Measurement more accessible to these organisations, as it has the power to provide solutions at scale, giving enterprises across the world a unified platform to measure and communicate their impact. This two-phased study leveraged the power of mixed-methods research to gain an understanding of the impact measurement adoption behaviour of South African SMMEs. Phase 1 was initiated with the utilization of a Partial Least Squares – Structured Equation Model (PLS-SEM) based on the framework of the Technology Acceptance Model (TAM) using a sample size of 90 SMMEs. This was followed by interviewing candidates and using a deductive qualitative research approach to create an understanding of their adoption behaviour based on the Technology, Organisation, Environment (TOE) framework. Furthermore, the second phase of the study made use of a systematic review based on Kuo et al.'s adapted PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses), followed by interview questions regarding user requirements to identify the appropriateness of existing impact measurement technologies in the South African SMME market. The first phase of the study revealed that even though SMMEs are aware of the significant impact they have on society, it is often based on informal measurement techniques and subjective opinion. This is mainly due to a lack of understanding of what impact measurement means, or how to even go about it. Furthermore, this is reinforced by the strong influence of social norms in this emerging impact economy, where there is very little emphasis or expectation to provide robust impact measurement. The main drivers of impact measurement adoption were found to include the affordability, the business' intent on creating impact and that businesses are likely to adopt impact measurement if there is a perceived value in doing so. The second phase of the study revealed that some of the major drivers behind the lack of adoption of Impact Measurement Software is the lack of awareness on available platforms, the lack of understanding of how to measure the impact, and finally the prohibitively high cost of acquiring the software – even though there isn't necessarily one piece of software that fits all requirements, it was found that there are various platforms that do meet the needs of South African SMMEs in some ways. This study has added to the knowledge of understanding the behaviour on impact measurement adoption among South African SMMEs and scoped the field of suitable, available technologies in a time where it is critical to rebuild the economy in a more equitable and impact-driven approach, after the devastating economic impact of COVID-19.